Personal connections in the digital age - Baym, Nancy K. (Malden, MA : Polity Press, 2015)
"Fully updated to reflect new developments in social media and digital scholarship, the book identifies the core relational issues these media disturb and shows how our talk about them echoes historical discussions about earlier communication technologies. Chapters explore how we use mediated language and nonverbal behavior to develop and sustain communities, social networks, and new relationships, and to maintain existing relationships in our everyday lives." -- Publisher information
New forms of personal connection -- Making new media make sense -- Communication in digital spaces -- Communities and networks -- New relationships, new selves? -- Digital media in everyday relationships -- Conclusion : The myth of cyberspace.
Revised edition of the author's Personal connections in the digital age, published in 2010.
Includes bibliographical references (pages 180-211) and indexes.
Keywords: Interpersonal relations; Interpersonal relations -- Technological innovations; Internet -- Social aspects; Cell phones -- Social aspects